Business Model Innovation as an Effort to Improve Marketing: Case Study in Rodokar, Yogyakarta - Yasmina Amalia; Yuliawati Yuliawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
To be able to excel in business competition in the culinary industry, MSME managers need to carry out good sustainable innovation. The aim of this research is to assist and improve the rodokar business. Research methods that can help business actors in designing a strategic plan is to use the Business Model Canvas. Data collection to carry out analysis on the Business Model Canvas was carried out by observation and interviews manager. Digitalization support activities marketing will be carried out in three stages: education, mentoring, and sustainability assessment. Training will given to increase partners' knowledge and understanding of various digital marketing platforms. The results of this activity are expected to expand partners' knowledge and understanding in the field of digitalization marketing. Mentoring activities are carried out to ensure partners are able to apply technology and training provided. In the end, the outcome that the partners want to achieve as business actors is an increase in partner economies of scale.